Computation of Crop Water Balance of Sorghum and Soyabean - Ranade, D.H.; Gupta, Ram K; Jain, L.K. (Journal of Soil and Water Conservation, 2022)
Wate balance along with Moisure Available Index (MAI) and Cumulative Water Requirement Satisfaction Index have been used to assess the water-stress condition vis-as-vis crop performance for Indore Region.